Chronic stress and emotion: Differential effects on attentional processing and recognition memory. (September 2019) - Wirkner, Janine; Ventura-Bort, Carlos; Schwabe, Lars; Hamm, Alfons O.; Weymar, Mathias
Highlights: Hair cortisol levels positively associated with late positive potentials. Chronic stress: Enhanced attentional processing during encoding of new stimuli. Impaired recognition memory (for emotional materials) following long-term stress. Opposite effects of chronic stress on neural correlates of attention and memory. Abstract: Previous research indicates that acute stress around the time of learning facilitates attention and memory for emotionally salient information. Despite accumulating evidence for these acute stress effects, less is known about the role of chronic stress. In the present study, we therefore tested emotional and neutral scene processing and later recognition memory in female participants using hair cortisol concentrations as a biological marker for chronic stress. Event-related potentials recorded during picture viewing indicated enhanced late positive potentials (LPPs) for emotional, relative to neutral contents. These brain potentials varied as a function of long-term hair cortisol levels: hair-cortisol levels were positively related to overall LPP amplitudes. Results from recognition memory testing one week after encoding revealed better memory for emotional relative to neutral scenes. Hair-cortisol levels, however, were related to poorer memory accuracy. Taken together, our results indicate that chronic stress enhanced attentional processing during encoding of new stimuli and impaired later recognition memory. Results are discussed with regard to putatively opposite effects of chronic stress on certain brain regions ( e.g ., amygdala and hippocampus).